Neuraminidases—Key Players in the Inflammatory Response after Pathophysiological Cardiac Stress and Potential New Therapeutic Targets in Cardiac Disease - Maren Heimerl; Thomas Gausepohl; Julia H. Mueller; Melanie Ricke-Hoch (Biology, 2022)
Glycoproteins and glycolipids on the cell surfaces of vertebrates and higher invertebrates contain α-keto acid sugars called sialic acids, terminally attached to their glycan structures. The actual level of sialylation, regulated through enzymatic removal of the latter ones by NEU enzymes, highly affects protein-protein, cell-matrix and cell-cell interactions. Thus, their regulatory features affect a large number of different cell types, including those of the immune system. Research regarding NEUs within heart and vessels provides new insights of their involvement in the development of cardiovascular pathologies and identifies mechanisms on how inhibiting NEU enzymes can have a beneficial effect on cardiac remodelling and on a number of different cardiac diseases including CMs and atherosclerosis. In this regard, a multitude of clinical studies demonstrated the potential of N-acetylneuraminic acid (Neu5Ac) to serve as a biomarker following cardiac diseases. Anti-influenza drugs i.e., zanamivir and oseltamivir are viral NEU inhibitors, thus, they block the enzymatic activity of NEUs. When considering the improvement in cardiac function in several different cardiac disease animal models, which results from NEU reduction, the inhibition of NEU enzymes provides a new potential therapeutic treatment strategy to treat cardiac inflammatory pathologies, and thus, administrate cardioprotection.